Lipidomics of plant and human opportunistic fungal pathogens of the genus Lasiodiplodia - Pedrosa, Bruna Silva (2021)
The fungal kingdom comprises many complex and dangerous, yet misunderstood species. Pathogenic fungi are known to cause several detrimental effects to plants, animals, and humans. Lasiodiplodia genus belongs to the Botryosphaeriaceae family and causes disease on a variety of plant hosts but has also been reported to cause infections in humans. Lasiodiplodia theobromae and Lasiodiplodia hormozganensis are fungal crosskingdom pathogens, meaning that they can repeatedly infect organisms from different kingdoms of life. It is known that lipids produced by pathogenic fungi have important roles in the host-pathogen relationship. In order to further understand the pathogenic behaviour of species of the genus Lasiodiplodia, the aim of this study was to fully characterize the lipidome of L. theobromae and L. hormozganensis. For this purpose, liquid and gas chromatography coupled to mass spectrometry technology were used to identify phospholipids, sphingolipids, triacylglycerols and fatty acids. The different lipids present in the lipidome of both fungal species amounted to 255 molecular species. Because most lipids identified are present in both fungi, the total of identifications made was of 423. Regarding phospholipids, 147 molecular species of the classes phosphatidylcholine, phosphatidylethanolamine, sphingomyelin, phosphatidic acid, cardiolipin, phosphatidylinositol, phosphatidylglycerol and phosphatidylserine were identified. Regarding sphingolipids, two ceramides were identified. In the triacylglycerol profile 83 molecular ions were identified, varying between TG C47 to C61. In the fatty acid profile 23 acids were identified, varying between FA C14 to C24. The most abundant fatty acids were C16:0, C16:1, C16:2, C18:0, C18:1, C18:2 and C18:3. Odd numbered fatty acids such as C15:0, C17:0 and C19:0 have also been observed in the lipidome of both species. In general, the lipidomic profiles of both species is very similar. This is the most complete study of the lipidome of Lasiodiplodia species until date. We hope this work can help to better understand fungal lipidomics and provide information on the lipids that constitute filamentous fungi, particularly plant pathogenic and human opportunistic species.